SIRT1 regulates tyrosine hydroxylase expression and differentiation of neuroblastoma cells via FOXO3a - Min-Ju Kim; Kyungsook Ahn; Seong‐Hoon Park; Hong-Jun Kang; Bong Geom Jang; Soo Jin Oh; Sun-Mee Oh; Yu‐Jin Jeong; Jee-In Heo; Jun‐Gyo Suh; Soon Sung Lim; Yoon-Jung Ko; et al. (2009)
To examine the function of SIRT1 in neuronal differentiation, we employed all‐trans retinoic acid (ATRA)‐induced differentiation of neuroblastoma cells. Nicotinamide inhibited neurite outgrowth and tyrosine hydroxylase (TH) expression. Inhibition of PARP or histone deacetylase did not inhibit TH expression, showing the effect to be SIRT1 specific. Expression of FOXO3a and its target proteins were increased during the differentiation and reduced by nicotinamide. FOXO3a deacetylation was increased by ATRA and blocked by nicotinamide. SIRT1 and FOXO3a siRNA inhibited ATRA‐induced up‐regulation of TH and differentiation. Taken together, these results indicate that SIRT1 is involved in ATRA‐induced differentiation of neuroblastoma cells via FOXO3a.